2005
DOI: 10.1002/mrc.1681
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed 180-GHz EPR/ENDOR/PELDOR spectroscopy

Abstract: Within this review, we describe a home-built pulsed electron paramagnetic resonance (EPR) spectrometer operating at 180 GHz as well as the incorporation of two double resonance techniques, electron nuclear double resonance (ENDOR) and pulsed electron double resonance (PELDOR), along with first applications. Hahn-echo decays on a TEMPO/polystyrene sample are presented, demonstrating that the observation of anisotropic librational motions is possible in a very precise manner at high magnetic fields. Bisdiphenyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 32 publications
(38 reference statements)
0
54
0
Order By: Relevance
“…The sensitivity 9,14 was measured with a 0.1% (by mass) sample of the organic radical TEMPOL (C 9 H 18 NO 2 ) in a polystyrene film. It has been suggested that TEMPOL may have a role in treating cancer 25 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sensitivity 9,14 was measured with a 0.1% (by mass) sample of the organic radical TEMPOL (C 9 H 18 NO 2 ) in a polystyrene film. It has been suggested that TEMPOL may have a role in treating cancer 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) experiments have realized new opportunities as magnetic fields have been increased 1,2,3,4,5,6,7 and pulsed capabilities have been added 8,9,10,11,12,13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, In order to compensate for hysteresis effects, the sweep of the magnetic field has to start at much lower (or higher) field position than the first resonance appears. Many other experiments, such as ENDOR [11,12], PELDOR [11] or DNP [13] require fixed, reproducible and stable magnetic field values, which are difficult to achieve at high magnetic fields using only control of the magnet or sweep coil current without any feedback loops.…”
Section: Introductionmentioning
confidence: 99%